The magic misfits - Harris, Neil Patrick, 1973-; Marlin, Lissy (New York : Little, Brown and Company, 2017)
"Six young magicians and illusionists team up to save their small town from a crooked carnival owner and his goons"--
Keywords: Magic tricks -- Fiction; Orphans -- Fiction; Carnivals -- Fiction; Robbers and outlaws -- Fiction; Conduct of life -- Fiction; Humorous fiction